Relevant CSR Activities for Strenghtening Social Profile of Metallurgical Company - Vávra, Jan; Bednaříková, Marie; Munzarová, Simona; Tetřevová, Liběna (TANGER, spol. s r.o., 2016)
The CSR concept covers the following five areas: the economic area, the social area, the environmental area, the ethical area and the philanthropic area. The benefits of CSR activities from the point of view of the company and its relevant primary and secondary stakeholders represent an intensively discussed topic. Proving relations between individual CSR activities and the success of the corporate operations is crucial for acceptance of CSR. Activities in the social area include application of responsible employee policy and consideration of the impacts of their products on health, working conditions, production and product safety, as well as protection of human rights and cultural heritage. The environmental area activities mainly include the environmental activities and instigation of initiatives promoting responsible approach to the environment, ensuring environment-friendly and sustainable production and consumption. The area of ethical business practice includes especially application of ethical behavior in compliance with legal and moral standards, fighting corruption. Philanthropic activities include usually corporate voluntary giving in the form of money giving or employee volunteerism. The paper deals with identification and evaluation of relevant CSR activities realized by metallurgical companies. The main objective is to determine relevant CSR activities to strengthen the social profile (or corporate social performance) of the company and whether metallurgical companies consider CSR activities as viable and useful tool for strengthening social profile and corporate social performance of the company.
Přijatelné CSR aktivity pro posílení sociálního profilu u metalurgických podniků
Keywords: Corporate social responsibility; reporting; social profile; Společenská odpovědnost firem; reporting; sociální profil podniku